Redesigning of Vortex Tube - Haqqani, Mohammed Hameeduddin; Azizuddin, Mohammed; Kiran, Rajamahanti Surya (Current Approaches in Engineering Research and Technology Vol. 10, 2024)
Ranque Hilsch Vortex Tube (RHVT) takes in the compressed air from the air compressor and releases hot air from one end and the cold end from the other end. Generally, any fluid dynamics takes place due to the law of conservation of mass, the law of conservation of energy, and the law of conservation of momentum. RHVT a Ranque Hilsch Vortex Tube is a unique thermo-fluidic and indisputable device for the purpose of the production of hot and cold temperatures without any mechanical aid. This method which is quite old in the industry for the application of centrifugal swirling of two fluids for the purpose of separation based on density. This method of cooling utilizes compressed air to be injected into a turbulent fixed-size of orifice tube with predefined lengths and diameters. The purpose of this work is to explore the various components requirements from the various literature that are available and to make a software model using Unigraphics. The methodology of this work has been divided into two parts. One part is to make a study on the existing designs from the literature reviews and the Second part is to frame the design specifications for the new design from the simplified, specified, standardized and diversified observations and transform it into a working model. In this paper, an attempt is being made to design a new RHVT device, the process starts with collecting the relevant and proven data on RHVT from the literature surveys in order to collect the suitable dimensions for the purpose of designing a new efficient smaller combined with unique features. Some of the reasons attributed to this kind of phenomenon of energy separation are the drop in the temperature due to the sudden expansion, centrifugal effect, secondary circulation and friction. The vortex tube could be used for the purpose of spot cooling of any area and machine cooling of moving equipment using industrial compressed air as the source. The use of compressed air makes the device less susceptible for breakdown due to the fact being no moving parts used in this system. There are also no proven facts of the existence of the chemical reactions within the vortex tube. From the results, it is evident that the RHVT design extensively depends on Inlet pressure of the air stream and the exit throttling on the hot end and cold end. The future work would be to Plan-Design-Develop-Manage Risks-Test-Produce-Release-Support by manufacturing a prototype and doing a Field/Factory setting for this product.